Poly(propylene carbonate)/poly(3‐hydroxybutyrate)‐based bionanocomposites reinforced with cellulose nanocrystal for potential application as a packaging material. (5th December 2019) - Jiang, Guo; Yu, Li; Zhang, Mengdi; Wang, Feng; Zhang, Shuidong
Abstract : Poly(propylene carbonate) (PPC) is an aliphatic polycarbonate synthesized from carbon dioxide and propylene oxide. Poly(3‐hydroxybutyrate) (PHB) is a type of thermoplastic polyester produced by biological fermentation. The blending of PHB with PPC can effectively enhance the mechanical properties and barrier properties of PPC. Bionanocomposites of PPC/PHB enhanced by cellulose nanocrystal (CNC) are prepared via a two‐step process using polyethylene glycol as a carrier. Results show that the oxygen barrier properties of the composites increased with the increase of the CNC content. When the CNC content is 1 wt%, the oxygen barrier performance increases nearly 18 times. The assumed model can predict the barrier performance of composites with the combined influence of morphology and CNC distribution. This will make PPC/PHB/CNC nanocomposites a very promising degradable material for food packaging application.